Organizational Culture as a Function of Predicting Administrative Competencies and Decision-making among the Top Leaders in Faculties of Physical Education and Sports Sciences from the Point of Teaching View - Jassem Jaber Mohammed (Journal of Global Pharma Technology, 2018)
The importance of this study is that it is concerned with the human resource, which is the secret of the success of any institution, especially the educational institution, which is the leadership of the senior leadership positions that are supposed to give the institution sufficient attention in all aspects, especially cultural ones, which affect the behavior of individuals in decision-making and their competence to work and thus influence On the work of the institution, as defined by the research community, which is represented by the top leaders of the faculties of physical education and sports sciences, and the total vocabulary of (40) single, was chosen from this community in a comprehensive manner.The researchers used the measure of administrative competencies, decision making and organizational culture, which was built by the researcher Talal bin Abdullah Hussein Al-Sharif in 2014. The scale consists of (38) paragraphs distributed as follows:The first dimension (planning): includes (11) paragraph, namely paragraphs: (1 to 11).The second dimension (organization): includes (9) paragraph, namely paragraphs: (12 to 20).The third dimension (communication): includes (9) paragraph,The fourth dimension (calendar): includes (9) paragraph, namely paragraphs: (30 to 38).It is possible to arrive at the following conclusions: The results of the efficiency of the model to predict the organizational culture of the top leaders of the faculties of physical education and sports sciences in management competencies and decision-making.Keywords: Organizational culture, Administrative competencies, Physical education and sports sciences.